Availability of less invasive prenatal, perinatal and paediatric autopsy will improve uptake rates: a mixed‐methods study with bereaved parents. (6th February 2019) - Lewis, C; Riddington, M; Hill, M; Arthurs, OJ; Hutchinson, JC; Chitty, LS; Bevan, C; Fisher, J; Ward, J; Sebire, NJ
Abstract : Objective: To investigate whether less invasive methods of autopsy would be acceptable to bereaved parents and likely to increase uptake. Design: Mixed methods study. Setting: Bereaved parents recruited prospectively across seven hospitals in England and retrospectively through four parent support organisations. Sample: Eight hundred and fifty‐nine surveys and 20 interviews with bereaved parents. Methods: Cross‐sectional survey and qualitative semi‐structured telephone interviews. Main outcome measures: Likely uptake, preferences, factors impacting decision‐making, views on different autopsy methods. Results: Overall, 90.5% of participants indicated that they would consent to some form of less invasive autopsy [either minimally invasive autopsy (MIA), non‐invasive autopsy (NIA) or both]; 53.8% would consent to standard autopsy, 74.3% to MIA and 77.3% to NIA. Regarding parental preferences, 45.5% preferred MIA, 30.8% preferred NIA and 14.3% preferred standard autopsy. Participants who indicated they would decline standard autopsy but would consent to a less invasive option were significantly more likely to have a lower educational level (odds ratio 0.49; 95% CI 0.35–0.70; P = 0.000062). Qualitative findings suggest that parents value NIA because of the lack of any incision and MIA is considered a good compromise as it enables tissue sampling while easing the parental burden associated with consenting to standard autopsy. Conclusion: Less invasive methods of autopsy are acceptable alternatives for bereaved parents, and if offered, are likely to increase uptake and improve parental experience. Further health economic, validation and implementation studies are now required to assess the viability of offering these in routine widespread clinical care. Tweetable abstract: Mixed methods UK study finds less invasive methods of autopsy are acceptable alternatives for bereaved parents, and if offered, are likely to increase uptake and improve parental experience. Tweetable abstract: Mixed methods UK study finds less invasive methods of autopsy are acceptable alternatives for bereaved parents, and if offered, are likely to increase uptake and improve parental experience.